Field evaluation of soybean transgenic event DAS-81419-2 expressing Cry1F and Cry1Ac proteins for the control of secondary lepidopteran pests in Brazil. (June 2017) - Marques, Luiz H.; Santos, Antonio C.; Castro, Boris A.; Moscardini, Valéria F.; Rossetto, Jaédino; Silva, Oscar Arnaldo N.; Zobiole, Luiz Henrique S.; Valverde-Garcia, Pablo; Babcock, Jonathan M.; Storer, Nicholas P.; Rule, Dwain M.; Fernandes, Odair A.
Abstract: Genetically modified soybean with transgenic event DAS-81419-2 (Conkesta™ technology), expresses two Bacillus thuringiensis ( Bt ) derived proteins, Cry1Ac and Cry1F. Event DAS-81419-2 is a proposed new Integrated Pest Management (IPM) tool with demonstrated high efficacy for controlling the primary lepidopteran pests affecting soybean production in South America. Studies were conducted in Brazil from 2011 to 2016 to assess the efficacy of DAS-81419-2 against secondary lepidopteran pests including Elasmopalpus lignosellus, Agrotis ipsilon and Helicoverpa armigera, using artificial infestations to ensure uniform pest pressure. Results from research trials across nine localities showed that compared to a non- Bt isoline, DAS-81419-2 significantly reduced the seedling stage plant mortality caused by E. lignosellus and the feeding damage caused by H. armigera during both vegetative and reproductive crop growth stages. Event DAS-81419-2 showed moderate activity on A. ipsilon, and additional control tactics such as a chemical insecticide applied as a seed treatment or spray during early crop stages may be needed against this pest to provide consistently higher levels of protection in fields that are at risk of infestation. Collectively, the efficacy of soybean transgenic event DAS-81419-2 for the control of secondary lepidopteran pests, added to its high efficacy on primary lepidopteran pests suggest this new, dual protein technology will be an important tool where primary and secondary pests affect soybean production. Highlights: DAS-81419-2 soybean was evaluated against some secondary lepidopteran pests. DAS-81419-2 soybean showed excellent activity on E. lignosellus and H. armigera. DAS-81419-2 soybean showed moderate activity on Agrotis ipsilon. Additional control tactics may be needed against A. ipsilon. This new technology will be an important tool within a robust soybean IPM program.